Pengaruh Penerapan model Pembelajaran Explicit Instruction Terhadap Motivasi Dan Hasil Belajar Siswa Kelas XI IPS Pada Pelajaran Ekonomi (Akuntansi) Di SMAN 1 Langgam Kabupaten Pelalawan - Elghina Silma (PEKBIS, 2017)
Target of this research is to know how big influence of applying of model study ofinstruction explicit in improving result and motivation learn class student of XI IPS[in] SMAN 1 Langgam. Subjek Research [is] class student of XI IPS 1. Datacollecting taken [is] practice problems and kuesioner. Result of research showapplied of model study of insrtuction explicit have an effect on in improving resultand motivation learn class student of XI IPS SMAN 1 Langgam.